2022
DOI: 10.1038/s41598-022-08698-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging reveals distinct brain glucose metabolism patterns associated with morphine consumption in Lewis and Fischer 344 rat strains

Abstract: Vulnerability to addiction may be given by the individual's risk of developing an addiction during their lifetime. A challenge in the neurobiology of drug addiction is understanding why some people become addicted to drugs. Here, we used positron emission tomography (PET) and statistical parametric mapping (SPM) to evaluate changes in brain glucose metabolism in response to chronic morphine self-administration (MSA) in two rat strains with different vulnerability to drug abuse, Lewis (LEW) and Fischer 344 (F34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Different brain metabolic patterns observed via PET imaging after morphine self-administration suggests differences in potential predisposition to morphine misuse between individuals. 55 …”
Section: Recent Developments With Established Neuroimaging Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different brain metabolic patterns observed via PET imaging after morphine self-administration suggests differences in potential predisposition to morphine misuse between individuals. 55 …”
Section: Recent Developments With Established Neuroimaging Techniquesmentioning
confidence: 99%
“…Different brain metabolic patterns observed via PET imaging after morphine self-administration suggests differences in potential predisposition to morphine misuse between individuals. 55 One group of researchers performed a data-driven study in 2022 to evaluate the predictive efficacy of resting-state functional magnetic resonance imaging (rs-fMRI) during early abstinence from alcohol dependency. 56 They reported that alcohol dependency was related to deficits in regional homogeneity of the left postcentral gyrus, low-frequency fluctuations of the right fusiform gyrus, and frontal cortex between the right fusiform gyrus and the right middle cingulum.…”
Section: Dovepressmentioning
confidence: 99%